Предмет: Математика,
автор: aida50
log7(x-2)+log7(x+2)=log7(4x+41)
Ответы
Автор ответа:
0
log{7}(x-2)+log{7}(x+2)=log{7}(4x+41)
log{7}(x^2-4)=log{7}(4x+41)
x^2-4=4x+41
x^2-4x-45=0
x1=11
x2=-5 - посторонний корень так как подлогарифмические выражения должны быть больше нуля
log{7}(x^2-4)=log{7}(4x+41)
x^2-4=4x+41
x^2-4x-45=0
x1=11
x2=-5 - посторонний корень так как подлогарифмические выражения должны быть больше нуля
Похожие вопросы
Предмет: Биология,
автор: tribovitvitovicm
Предмет: Английский язык,
автор: aliarashalieva10
Предмет: Английский язык,
автор: gulrozaturdalieva105
Предмет: Обществознание,
автор: Yanccik